ANALISIS STRATEGI GURU DALAM MENANAMKAN NILAI PENDIDIKAN KARAKTER PADA SISWA KELAS V DI SD BUDI MURNI 1 MEDAN - Stepi Agustina Sirait; Anton Sitepu; Joen Purba; Regina Sipayung; Rumiris Lumbangaol; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the habituation and role modeling strategies employed by teachers to instill character values at SD Budi Murni 1 Medan. The habituation strategies encompass reinforcing religious values, discipline, responsibility, environmental care, and honesty through structured and consistent daily routines and activities. Teachers not only teach character values theoretically but also exemplify them as living models for students to observe and emulate. Teacher role modeling, both in daily behavior and consistency between words and actions, plays a crucial role in shaping students' character. The results show that the combination of habituation strategies and teacher role modeling effectively cultivates religious, disciplined, responsible, environmentally conscious, and honest character traits among students. This approach educates not only through instruction but also holistically internalizes character values into students’ everyday lives.